An Introduction to traditional architecture of Bhutan / (Acc: 960) - Department of Works, Housing and Roads (Thimphu : Department of Works, Housing and Roads, 1993)
The vernacular architecture of a country reflects its culture, religion and identity. Researchers found that countries with similar culture and religion share few similar architectural characteristics. The most similar characteristic is the choice of building material used, where locally available materials such as earth, wood and bamboo are found to be used extensively. This paper explores the traditional architecture of few Asian countries with Buddhist culture viz. Bhutan, China, Japan, Laos, Myanmar, Nepal, Thailand and Vietnam; mainly focusing on its vernacular dwellings. The architectural features, organization of spaces and building materials of vernacular dwellings of these countries are also exploited.
Keywords: 1. Traditional architecture --Bhutan 2. Design --Bhutanese.